Biological diversity act 2002 Assam Biodiversity Rules 2010 (Book 3) - (:unkn) unknown (Assam State Biodiversity Board, Guwahati, 2012)
The book describes about the rich bio diversity of Assam and the Acts and rules passed by the government of Assam.
Keywords: Assamese; Biodiversity; Assamese; English